Gender equality principles in CEDAW: an Islamic perspective - Ahmad, Nadzrah (IIUM Press, International Islamic University Malaysia, 2017)
Misunderstanding of Islamic concept of gender equality by the West and some Muslims has caused Muslim women to be influenced by alien conception and principle of gender equality while seeking justice and freedom. As a result, some of these women lead movements that fight for gender equality contrasting to Islamic teaching. CEDAW is a result of such fight and it is presently finds its way penetrating into national policy worldwide and this includes Muslim countries. Consequently, it gives rise to the issue of practicing religious law in some of these countries. This calls for a need to clarify the understanding of the issue at fundamental level. Therefore, the concept of gender equality shall be examined thoroughly under the light of both views; CEDAW and the Islamic ones (Quran and Sunnah).